1983
DOI: 10.1007/bf00964729
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of 5-hydroxytryptamine release from superfused synaptosomes by 5-hydroxytryptamine and its immediate precursors

Abstract: The effect of L-tryptophan, 5-hydroxy-L-tryptophan (5-HTP), and 5-hydroxytryptamine (5-HT) on the K+-evoked release of [3H]5-HT from superfused rat brain synaptosomes was studied. 5-HT at concentrations above 10 nM significantly inhibited the K+-evoked release of [3H]5-HT. A slight enhancement of [3H]5-HT release was observed at a concentration of 5nM. In contrast tryptophan at a concentration of 10 nM significantly enhanced [3H]5-HT release with little effect at higher concentrations. 5-HTP did not significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In rats, relevant oral doses of 5-HTP (given without the coadministration of MAO inhibitors) result in increased 5-HTP and 5-HT immunoreactivity in the dorsal raphe nucleus, suggesting that 5-HTP is effectively transported across the blood-brain barrier and decarboxylated into 5-HT (Lynn-Bullock et al, 2004). Although several animal studies have demonstrated that 5-HTP administration can increase 5-HT levels in the central nervous system (reviewed in Lynn-Bullock et al, 2004), it remains unknown if these increases reflect functionally meaningful synaptic 5-HT release and stimulation of 5-HT activity over the long term (Meyers, 2000), or if enhancements in 5-HT release are unlikely due to regulation by autoreceptors (Suter and Collard, 1983).…”
Section: Introductionmentioning
confidence: 98%
“…In rats, relevant oral doses of 5-HTP (given without the coadministration of MAO inhibitors) result in increased 5-HTP and 5-HT immunoreactivity in the dorsal raphe nucleus, suggesting that 5-HTP is effectively transported across the blood-brain barrier and decarboxylated into 5-HT (Lynn-Bullock et al, 2004). Although several animal studies have demonstrated that 5-HTP administration can increase 5-HT levels in the central nervous system (reviewed in Lynn-Bullock et al, 2004), it remains unknown if these increases reflect functionally meaningful synaptic 5-HT release and stimulation of 5-HT activity over the long term (Meyers, 2000), or if enhancements in 5-HT release are unlikely due to regulation by autoreceptors (Suter and Collard, 1983).…”
Section: Introductionmentioning
confidence: 98%
“…Measurement ofS-HT releasefrom superfused synaptosomes Male Albino Wistar rats weighing between 200 and 250g were used in all studies. The methods used to prepare synaptosomes and measure the release of [3H]-5-HT have been described in detail elsewhere (Collard et al, 1981;Suter & Collard, 1983). Synaptosomes were prepared from rat forebrain by the method of Gray & Whittaker (1962) and incubated with 0.1 pM [3H]-5-HT (specific activity 18-19.8Cimmol-1) for 10min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…The efflux of [3H]-5-HT was expressed as a percentage of tissue [3H]-5-HT released per fraction. The release in response to a given degree of depolarisation was calculated as the total [3H]-5-HT released above the baseline during the application of the K+ pulse (Suter & Collard, 1983).…”
Section: Methodsmentioning
confidence: 99%
“…A recent investigation by Gendle and Golding () demonstrated that exogenous 5‐HTP impaired decision making during the first 20 trials of the Iowa Gambling Task (IGT), when participants were forming an “attentional set” that encapsulated the rules of the task (Bechara et al ., ; Robbins and Roberts, ). Although the most parsimonious explanation of these findings is that 5‐HTP increased synaptic 5‐HT release in the PFC and that this release impaired decision making during early IGT trials, this possibility seems unlikely given the regulation of 5‐HT release by autoreceptors (Suter and Collard, ).…”
Section: Introductionmentioning
confidence: 99%